Open educational resources: peluang untuk belajar mandiri Bahasa Jerman di era Covid-19 - Wijayati, Primardiana Hermilia; Hidayat, Edy; Kartika A, Dewi; M.Kharis, M.Kharis (2020)
Open Educational Resources provide opportunities for German language teachers and learners to take advantage of freely available materials. Teachers can adopt, adapt, or change German-language materials on pages marked with OER for teaching purposes freely without worrying about being sued for copyright infringement. Learners can access materials for independent study at any time without having to pay. This study aims to map the German language material available on the OER website. The data were collected using document observation techniques, and the analysis used was content analysis. The results show that most of the OER pages provide structure and vocabulary material in German. There is very little material related to reading skills and no material to guide speaking and writing exercises.